Vertical-Axis Differential Drag Windmill - Tedjo Narsoyo Reksoatmodjo (Jurnal Teknik Mesin (Sinta 3), 2004)
Eventhough the development of national electricity in Indonesia rapidly in- creased, but in reality it does not reach the remote villages. The reason is that the establishment of electricity network to reach the remote villages is much more expensive than the revenues gained from the customers. Indonesia as an archipelagos stretch along the equator, the wind to be the source of energy blows throughout the years both in lands and seas. Therefore a simple small scale wind power generator is considered to be the best solution to provide electricity for the remote village communities. Abstract in Bahasa Indonesia : Walaupun pembangunan perlistrikan nasional cukup pesat, namun pada kenyataannya belum dapat menjangkau desa-desa terpencil. Hal ini disebabkan biaya untuk pembangunan jaringan transmisi listrik ke desa-desa terpencil jauh lebih mahal daripada pendapatan yang diperoleh dari pelanggan di desa-desa ter- pencil tersebut. Indonesia sebagai negara kepulauan, angin merupakan sumber energi yang tersedia sepanjang tahun baik di darat maupun di lautan. Oleh sebab itu suatu pembangkit listrik tenaga angin (PLTAn) berskala kecil dengan konstruksi sederhana dan mudah pemeliharaannya merupakan solusi yang bisa dioperasikan sendiri oleh masyarakat pedesaan. Kata kunci: pembangkit tenaga listrik, turbin angin, turbin angin deferensial sumbu vertical.